Perkawinan Usia Dini Perempuan Korowai di Kampung Kabuage Distrik Firiwage Kabupaten Boven Digoel - Sarova Kenelek; Agustina Ivonne Poli; Simon Abdi K. Frank (Universitas Cenderawasih, 2020)
This study aims to determine the form of early marriage among Korowai women and want to know the factors that influence the occurrence of early marriage for Korowai women in Kabuage village, Firiwage district, Boven Digoel district. The research method used is descriptive-qualitative method, because this method is considered capable of analyzing social reality in detail. Research informants include women who marry early, traditional parents, men and the village head. Data collection was carried out using literature study and field study techniques which included observation, interviews and literature studies. In analyzing the data, three lines of interactive analysis were used, namely data reduction, data presentation and conclusion drawing. The results showed that there were two forms of early marriage in women, namely the form of coercion and without coercion and the driving factors for early marriage in women in Kabuage Village were cultural, educational, economic and modernization factors. The conclusions and suggestions of this study are that early marriage among Korowai women in Kabuage Village, Firiwage District, Boven Digoel Regency occurs in the form of coercion and without coercion which generally occurs due to cultural, educational, economic and modernization factors. Then the suggestion that can be given is the need for the involvement of the Office of Women Empowerment and Family Planning (KB) in Boven Digoel Regency to suppress marriage at an early age. So, it can provide a good understanding to parents, community and traditional leaders. As well as creating more opportunities for girls to obtain rights in accordance with the Rights of the Child Convention. As well as the need for the efforts of various agencies to work together to help human resources in Kabuage Village.